2017
DOI: 10.1007/s10103-017-2247-1
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy controls of Staphylococcus aureus intradermal infection in mice

Abstract: Infections caused by Staphylococcus aureus lead to skin infections, as well as soft tissues and bone infections. Given the communal resistance to antibiotics developed by strains of this bacterium, photodynamic therapy emerges as a promising alternative treatment to control and cure infections. Females of the Balb/C mice were infected with 10 CFU of methicillin-resistant S. aureus (MRSA) and divided into four distinct groups: P-L- (negative control group), P+L- (group exposed only to curcumin), P-L+ (group exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Selection of resistant strains can be limited by combined therapy—simultaneous use of at least two antibiotics/agents that affect different molecular targets [14,15]. Another interesting approach for the treatment of infectious disease is photodynamic therapy [16,17] and some research groups developed new vaccines that seem to be effective in the prophylaxis of staphylococcal infections [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of resistant strains can be limited by combined therapy—simultaneous use of at least two antibiotics/agents that affect different molecular targets [14,15]. Another interesting approach for the treatment of infectious disease is photodynamic therapy [16,17] and some research groups developed new vaccines that seem to be effective in the prophylaxis of staphylococcal infections [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Ermolaeva et al have shown that atmospheric cold plasma causes intracellular damage of S. aureus and allows inactivating bacteria by strong oxidative stress [ 12 ]. As an alternative, the potency of photodynamic therapy was highlighted by Almeida et al and a first report on the efficacy of curcumin showed that photodynamic therapy may be effective against MRSA infections [ 13 ]. Reports on the bioelectric inhibitory effects of low and high frequency electric currents are also available [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the bioelectric inhibitory effects of low and high frequency electric currents are also available [ 14 , 15 ]. Nevertheless, the available methodologies have limitations such as a long time of exposure [ 14 ], the requirement to use photosensitizers [ 13 ] or other undesired side effects [ 16 ]. In this study, we extend the array of effective bacteria inactivation methodologies by providing data on the inactivation efficacy of electroporation in combination with typical antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with what is observed in vitro, PDT can be highly successful at eradicating S. aureus within the host; however, this is greatly dependent on the photosensitizer, light source, and duration of exposure chosen (183). Nonetheless, PDT has been shown to effectively deplete bacterial levels and decrease wound healing time in superficial skin infections using murine skin abrasion and burn wound models, as well as to reduce bacterial burdens in deeper soft tissue abscesses (184189). Using fiber optic light delivery systems, PDT treatment has also been quite effective against S. aureus osteomyelitis in rats (190193).…”
Section: Photodynamic Therapymentioning
confidence: 99%